2021
DOI: 10.1177/03635465211042633
|View full text |Cite
|
Sign up to set email alerts
|

Autograft Versus Allograft: The Evidence in Hip Labral Reconstruction and Augmentation

Abstract: Background: Labral augmentation and labral reconstruction have emerged as essential procedures for restoring the anatomic and functional characteristics of the hip joint in patients with a deficient hip labrum or irreparable labral tear. Hypothesis/Purpose: The purpose of this study was to compare allograft and autograft hip labral reconstruction and augmentation. We hypothesized that autografts would entail fewer revision arthroscopic procedures. Study Design: Cohort study; Level of evidence, 3. Methods: Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Additionally, the rate for secondary surgeries was also comparable. Previously, Cooper et al 10 reported results comparing iliotibial band autografts and allografts, with 150 and 55 patients in each group, respectively. The mean follow-up time was 3.3 6 1.2 years and 4.2 6 1.6 years for the allograft and autograft groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the rate for secondary surgeries was also comparable. Previously, Cooper et al 10 reported results comparing iliotibial band autografts and allografts, with 150 and 55 patients in each group, respectively. The mean follow-up time was 3.3 6 1.2 years and 4.2 6 1.6 years for the allograft and autograft groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive labral calcification, insufficient viable labral tissue (<6 mm), and iatrogenic labral insufficiency was considered irreparable. 6 Labral reconstruction with iliotibial band or gracilis autograft from the operative side was considered in the case of an irreparable labral tear. 4 , 24 …”
Section: Methodsmentioning
confidence: 99%
“…Extensive labral calcification, insufficient viable labral tissue (<6 mm), and iatrogenic labral insufficiency was considered irreparable. 6 Labral reconstruction with iliotibial band or gracilis autograft from the operative side was considered in the case of an irreparable labral tear. 4,24 Chondroplasty was performed for partial-thickness cartilage lesions and chondral flaps with an arthroscopic shaver and/or electrocautery device (Smith & Nephew).…”
Section: Surgical Techniquementioning
confidence: 99%
“…24,28 The use of these autografts requires express authorization from the patient through informed consent and can also lead to possible morbidity in the donor area and an increase in surgical time. 2,7,9 As an alternative to human tissue usage, biodegradable, synthetic, polyethylene scaffolds were developed more than 15 years ago for restoration of the meniscus in the knee, with successful results clinically up to 10 years. 3,6,15,41 Owing to the abundant vascular supply in the acetabulum, 33 integration of the scaffold can be expected.…”
mentioning
confidence: 99%
“…24,28 The use of these autografts requires express authorization from the patient through informed consent and can also lead to possible morbidity in the donor area and an increase in surgical time. 2,7,9…”
mentioning
confidence: 99%